CSR as a Tool for Marketing and HR Engagement: Aligning Social and Business Goals - Reina A. Hadikusumo (Arbain Publishing, 2025)
This study explores Corporate Social Responsibility (CSR) as an effective tool for marketing and human resource (HR) engagement, emphasizing the alignment of social and business goals. Utilizing a qualitative literature review approach, the research synthesizes existing studies, theoretical frameworks, and practical examples to examine how CSR initiatives can simultaneously enhance brand reputation, consumer loyalty, and employee motivation. The findings reveal that CSR activities, when strategically integrated into marketing and HR practices, foster stronger emotional connections with both external and internal stakeholders. From a marketing perspective, CSR enhances brand authenticity and differentiation, leading to increased consumer trust and advocacy. From an HR standpoint, CSR initiatives contribute to employee engagement by promoting organizational pride, job satisfaction, and a shared sense of purpose. The study also highlights the importance of aligning CSR efforts with core business objectives to ensure sustainability and maximize impact. Challenges such as balancing stakeholder expectations and measuring CSR outcomes are discussed, along with best practices for effective implementation. This research contributes to the growing body of knowledge on CSR’s dual role in business strategy and organizational development, offering practical insights for managers seeking to leverage CSR as a means to achieve both social responsibility and competitive advantage. The study underscores the critical need for integrated CSR approaches that bridge marketing and HR functions to create cohesive and sustainable value for businesses and society.